Thermal distribution and magnetic stability relation in ferromagnetic ising thin films: Monte carlo and finite element analysis - Supatutkul C. (Taylor and Francis Ltd., 2014)
This work studied the magnetic stability related to thermal distribution of heat pulse applying on FePt thin films using Monte Carlo simulation and Finite Element Method. The Ising model was used to represent magnetic characteristic of FePt in the calculation. The results show that the heat mostly diffuses downwards to the coupled heat sink, which causes the highest thermal gradient in this direction. Therefore, magnetization within this heating area decreases while the magnetization in the other area preserves its magnitude. © 2014 Taylor & Francis Group, LLC.